America's secret jihad : the hidden history of religious terrorism in the United States - Wexler, Stuart (Berkeley, California : Counterpoint, 2015)
"The conventional narrative concerning religious terrorism inside the United States says that the first salvo occurred in 1993, with the first attack on the World Trade Center in New York City. This narrative has motivated more than a decade of wars, and re-prioritized America's domestic security and law enforcement agenda. But the conventional narrative is wrong. A different group of jihadists exists within US borders. This group has a long but hidden history, is outside the purview of public officials and has an agenda as apocalyptic as anything Al Qaeda has to offer. Radical sects of Christianity have inspired some of the most grotesque acts of violence in American history: the 1963 Birmingham Church bombing that killed four young girls; the "Mississippi Burning" murders of three civil rights workers in 1964; the assassination of Martin Luther King, Jr. in 1968, the Atlanta Child Murders in the late 1970s; and the Oklahoma City Bombing in 1995. America's Secret Jihad uses these crimes to tell a story that has not been told before. Expanding upon the author's ground-breaking work on the Martin Luther King, Jr. murder, and through the use of extensive documentation, never-before-released interviews, and a re-interpretation of major events, America's Secret Jihad paints"--
"Present[s] a picture of Christian extremism. [The book] focuses on a group of dedicated religious zealots who co-opted major elements of the Ku Klux Klan and other white supremacist groups for a frightening agenda: an apocalyptic race war within the United States. This group has a long but hidden history, is outside the purview of public officials and has an agenda as heinous as anything Al Qaeda has to offer. These radical sects of Christianity have inspired some of the most grotesque acts of violence in American history: the 1963 Birmingham Church bombing that killed four young girls; the "Mississippi Burning" murders of three civil rights workers in 1964; the assassination of Martin Luther King, Jr. in 1968, the Atlanta child murders in the late 1970s; and the Oklahoma City bombing in 1995. Expands upon the author's ground-breaking work on the Martin Luther King, Jr. murder, and the Birmingham bombing tragedy-- and uses extensive documentation and never-before-released interviews, as well as a re-examination of major events-- to expose the significant influence of the Christian Identity movement on white supremacist organizations." --
Argues that theologians of the Christian Identity movement have motivated much domestic white supremacist terrorism since the 1950s and not, as scholars have written, only since 1983.--
Twisted theology: the synagogue bombings of 1957-1958 -- Genesis: the Christian identity movement -- The days of Noah: the 1962 Ole Miss integration riots and the 1963 murder of Medgar Evers -- The desecrated sanctuary: the 1963 Sixteenth Street Baptist Church bombing -- The blood of martyrs: the 1964 (Neshoba County) Mississippi burning murders -- The grapes of wrath: Black militant reaction and the urban riots of 1964-1965 -- The alpha: the failed attempts to assassinate Martin Luther King, Jr. 1958-1967 -- The omega: the final plot to assassinate Martin Luther King, Jr. 1967-1968 -- Tribulation: outrage and the investigation into who really killed King -- The end of an age: the fragmentation of the radical right in the 1970s -- The tenth plague: the Atlanta child murders, 1979-1981 -- Jeremiah's warriors: the Order, the CSA, and the 1984 murder of shock jock Alan Berg -- Tim McVeigh's Bible: the 1995 Oklahoma City bombing -- Zealous for honor: lone-wolf terrorism through the new millenium -- Revelations: apocalyptic religious terrorism post-9/11.
Includes bibliographical references (pages 377-404) and index.
Keywords: Terrorism -- United States -- Religious aspects; Violence -- United States -- Religious aspects; White supremacy movements -- United States -- Religious aspects; Ku Klux Klan (1915- ) -- History; Christian Identity (Sect) -- History